Digital Da'wah Strategies of Arrahmah.Id in Online Journalism - Hidayat, Tatang; Masitoh, Bilqisti Nur; Istianah, Istianah (Universitas Muhammadiyah Mataram, 2024)
Abstract: The increasing volume of technology and digitalization, Islam comes with an Islamic da'wah mission that facilitates the expansion of information and communication, one of which is the role of journalism in conveying da'wah treatises through digital website platforms. The purpose of this study was to analyze the digital da'wah strategy of arrahmah.id in online journalistic da'wah. This research uses a qualitative approach through observation and observation by collecting data, developing descriptive analysis methods. Based on the results of the study, arrahmah.id is one of the Islamic sites that is not just the delivery of religion but also civilization and the development of Islamic thought. Through the presentation of various contents and features, it makes it easier for madu' readers to find information and news about the Islamic world in the national and international arena. The implication will ignite the enthusiasm of Muslims in upholding Rahmatan lil Alamin and Izzatul Islam to stick to the Qur'an and As Sunnah.Abstrak: Semakin tingginya volume teknologi dan digitalisasi, Islam hadir dengan misi dakwah Islamiyah yang mempermudah perluasan informasi dan komunikasi, salah satunya peran jurnalistik dalam menyampaikan risalah dakwah melalui platfom digital website. Tujuan penelitian ini untuk menganalisis strategi dakwah digital dakwah arrahmah.id dalam dakwah jurnalistik online. Penelitian ini mengunakan pendekatan kualitatif melalui observasi dan pengamatan dengan mengumpulkan data, mengembangkan metode analisis deskriptif. Berdasarkan hasil penelitian, arrahmah.id merupakan salah satu situs Islam yang bukan sekedar penyampaian agama namun juga peradaban dan pengembangan pemikiran Islam. Melalui sajian konten dan fitur yang bermacam-macam memudahkan pembaca madu’ dalam mencari informasi dan berita seputar dunia Islam di kancah nasional maupun internasional. Implikasinya akan membakar semangat kaum muslimin dalam menegakkan Rahmatan lil Alamin dan Izzatul Islam untuk tetap berpegang teguh pada Al Qur’an dan As Sunnah.